Robotics in Japanese elderly care - attitudes of young university students and the Japanese government, and their implications - Siivonen, Johanna (My University, 2021)
Japan is facing a serious challenge in unprecedented scale: the aging society. With low fertility rates and increased life expectancy, the Japanese government needs to find solutions to the challenging situation. The purpose of this study is to identify what kind of similarities and differences the young Japanese university students belonging to the millennial generation and the Japanese government have in terms of attitudes and actions towards the usage of robots in Japanese elderly care. This study is conducted as qualitative research with a mixed methodology by analyzing official government documents regarding government policies and initiatives and by distributing an online questionnaire using closed, semi-closed, and open questions to Japanese university students belonging to the millennials generation. Participants include twelve respondents currently studying at Osaka Gakuin University in Osaka, Japan. The data acquired from both the official government documents and the questionnaire is analyzed by using content analysis. The study found out that the Japanese government has proposed many policies and initiatives in the field of robotics and is eager to promote robots as a solution not only to social problems such as shortage of professional care workers but also as an industry that can boost Japan’s stagnated economy through technological innovations. The Japanese government seems especially interested in applying robots to the elderly care industry in their efforts to shift long-term care from institutions to mote community-based care. However, the young Japanese university students demonstrated wariness towards the usage of robots in elderly care, although they shared the government's interest in community-based care. The findings also suggest that there seems to be a change happening in the current attitudinal environment in Japan regarding the care of the elderly. A larger-scale research on attitudes of the young Japanese university students to-wards the usage of robots and their general attitudes towards caregiving could be beneficial, and this study provides a solid founding for further studies on this topic.
Keywords: Japanese millennials, University students, Japan, Aging society, Elderly care, Care robots, Attitudes, Japanese government, Attitudinal environment